CONCEPT OF FEMALE DORMITORY BEDROOMS BASED ON STUDENTS’ PREFERENCE AND ADAPTATION - Mimin Aminah Yusuf; Arina Hayati; Muhammad Faqih (Journal of Architecture&ENVIRONMENT, 2018)
In Indonesia, type B non-affiliated organization Pesantren is represent private boarding school which is managed by organizationl or non-organizational Islamic institution. The Pesantren buildings are commonly not well designed and depended on institution’s preference. This paper investigates the bedroom design of the student’s dormitory based on student’s preferences and adaptation as reference the concept design. Bedroom is the smallest environmental scale of pesantren, yet it has great influence on accommodating student’s daily needs. Moreover, the bedroom dimension in Pesantren’s dormitory has limited area with higher occupant density compared to other dormitories. This study uses case study strategy supported by quantitative and qualitative methods. Six Pesantrens is chosen to determine bedroom’s design typology that is examine in 500 respondents in Sunan Drajat pesantren with questioner to identify student preference. After preference is known, adaptation be investigated. The result shows that almost all standards in typology of architectural elements are not available in pesantren. In this study, the typology used is based on existing observation in six Pesantren. Thus, the preference result is not ideal preference but potential preference. This study indicates that the need for student is influenced by security, privacy, personal space, territory, crowding and density. The suitability of student preference on bedroom size, number of occupant and bedroom wide per-student in their dormitory is very low, hence student has high adaptation. The type of adaptation that student used is by reaction, by adjustment and by withdrawal. The generated concept is room wide (student per square meter), arrange tool and furniture, room use space, room-wide based on a number of occupants, and mezzanine concept.